Depolarized SnO2-based gas anodes for electrowinning of silver in molten chlorides - Xiao S.; Haarberg G.M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
SnO2-based porous anodes were prepared and the behavior of gas bubbles on the porous anodes with different original coarse grain size, immersed in ethanol to simulate molten chlorides, was primarily investigated. SnO2-based porous anodes were used as gas anodes for the electrowinning of silver in CaCl2-NaCl-CaO-AgCl melts at 680°C. Hydrogen was introduced to the anode/electrolyte interface through the gas anode. Carbon was used as the cathode. Obvious depolarization of the anode potential was observed after the introduction of hydrogen comparing with no reducing gas introduced, indicating the involvement of hydrogen in the anode reaction. Metallic silver was deposited on the cathode.